(untitled) (New York, 2009)
This volume gives an overview of research done by CCI faculty in the area of Information and Intelligent Systems. Presented papers focus on recent advances in four major directions: Complex Systems, Knowledge Management, Knowledge Discovery, and Visualization. A major reason for producing this book was to demonstrate a new, important thrust in academic research where college-wide interdisciplinary efforts are brought to bear on large, general, and important problems. As shown in the research described here, these efforts need not be formally organized joint undertakings (through parts could be) but are rather a convergence of interests around grand themes. Taken together, the sections and chapters in this book reveal a variety of methods and tools that can be applied to quite diverse types of data and analysis problems but where each produces knowledge and features that can be combined, organized, explored, understood, and used in common ways (for example, through interactive visualization interfaces).
Keywords: Artificial intelligence,Trí thông minh nhân tạo